Galatians, Ephesians - Bray, Gerald L. (Reformation Commentary on Scripture Series, 2011)
Cover -- Title Page -- Contents -- Abbreviations -- General introduction -- Goals -- Perspectives -- Historical Context -- Patterns of Reformation -- Schools of Exegesis -- Reading Scripture with the Reformers -- A Guide to Using This Commentary -- Pericopes of Scripture -- Overviews -- Topical Headings -- Identifying the Reformation Texts -- The Footnotes -- Introduction to Galatians & Ephesians -- The Pauline Epistles in the Reformation Era -- Galatians and Its Interpreters -- Ephesians and Its Interpreters -- Principles of This Edition -- Commentary on Galatians -- Preface -- 1:1-5 Greetings and Blessings -- General Introduction to the Chapter -- 1:1 An Apostle Sent by God -- 1:2 Paul and His Brothers Write to the Churches in Galatia -- 1:3 Paul Blesses the Churches -- 1:4 Jesus Gave Himself for Our Sins -- 1:5 Glory Be to God -- 1:6-9 The Integrity of the Gospel -- 1:6 The Defection of the Galatians -- 1:7 Perverting the Gospel of Christ -- 1:8 An Angel Who Preaches Another Gospel -- 1:9 Paul Repeats His Condemnation -- 1:10-17 Paul's Conversion -- 1:10 No One Can Serve Two Masters -- 1:11 The Gospel Is Not a Human Invention -- 1:12 Paul Received the Gospel by a Revelation from Jesus Christ -- 1:13 Paul Once Persecuted the Church of God -- 1:14 Paul Was Zealous for the Traditions of His Ancestors -- 1:15 God Called Paul by Grace -- 1:16 God Chose Paul to Preach Christ Among the Gentiles -- 1:17 Paul Went to Arabia and to Damascus -- 1:18-24 The Journey to Jerusalem -- 1:18 Paul Went to Jerusalem -- 1:19 Paul Saw Only James, the Lord's Brother -- 1:20 Paul Is Not Lying About His Past -- 1:21 Paul Went to Syria and Cilicia -- 1:22 Paul Was Personally Unknown to the Churches of Judea -- 1:23 The Judean Churches Had Heard About Paul's Conversion -- 1:24 The Judean Churches Praised God -- 2:1-10 The First Visit to Jerusalem